Tachydromia punctifera Holarctic - Shamshev, Igor V.; Grootaert, Patrick (Zenodo, 2024)
Tachydromia punctifera (Becker) (Fig. 15) Tachista punctifera Becker, 1900: 32. Type localities: Russia, Krasnoyarskiy Territory, “Island Nikander” and “Dudinka”. Tachydromia punctifera : Chvála, 1975: 240 (♂). Notes on type series. Becker (1900) noted the following material: “ 3 Weibchen [female] von der Insel Nikander und Dudinka. (Sahlberg)”. Chvála (1970) examined one syntype from Becker’s Collection in Berlin. A second syntype is deposited in Helsinki (MZH) and it was examined by I.S. in 2019. The depositary of the third syntype (taken from “Island Nikander”) is unknown. The syntype in Helsinki bears a lectotype label (red, hand-written). However, this designation was never published. Material examined. NORTH AMERICA. CANADA. Nunavut: Chesterfield, 21.vii.1950, J. R. Vockeroth (1 ♂, 2 ♀, CNC); same locality, 30.vii.1950, J. R. Vockeroth (6 ♂, 5 ♀, CNC); same locality, 28.vii.1950, J. R. Vockeroth (1 ♂, CNC); same locality, 12.viii.1950, J. R. Vockeroth (1 ♀, CNC); same locality, 9.viii.1950, J. R. Vockeroth (1 ♀, CNC); same locality, 15–16.viii.1950, J. R. Vockeroth (1 ♂, 2 ♀, CNC); Coral Harbour, 15– 16.viii.1959, W. R. M. Mason (1 ♀, CNC). Yukon: Dempster Hwy, km 95, swept from stream edge, 19.vii.1982, D.M. Wood (1 ♀, CNC). USA. Alaska: Cape Thompson, 22–25.vii.1961, R. Madge (1 ♂, 4 ♀, CNC). EURASIA . RUSSIA. Chukotka Autonomous Okrug: Chukotka, upper flow of river Kanchalan, 1974, A. Kischinskiy (1 ♂, 1 ♀, ZISP). Krasnoyarskiy Territory: Medvezhiy, env. Norilsk, 6.vii.1967, Gorodkov (1 ♀, ZISP). Sakha (Yakutia) Republic: Chokurdakh, swampy floodplain of river Indigirka, 7.viii.1972, Gorodkov (1 ♀, ZISP). Diagnosis. The species is distinguished by the following combination of characters: palpus lacking black, subapical seta; legs almost uniformly dark brown; proepisternum pruinose only on lower portion. Male: palpus bicoloured, not divided into two lobes apically, strongly broadened and flattened on apical black portion. Redescription. Male (Fig. 15A). Length: body 2.2–2.3 mm, wing 2.2 mm. Head black, ...